A positive feedback loop of miR-30a-5p-WWP1-NF-κB in the regulation of glioma development. (July 2019) - Zhao, Peichao; Wang, MengMeng; An, Jiyang; Sun, Hongwei; Li, Tianhao; Li, Dongming
Abstract: Previous studies demonstrated that miR-30a-5p promotes glioma cell growth and invasion. Furthermore, WWP1 (WW domain containing E3 ubiquitin protein ligase 1) inhibits NF-κB activation that is strongly correlated with gliomagenesis. Using the GEO database and bioinformatics analyses, we identified WWP1 was downregulated in glioma tissues and might be a putative target for miR-30a-5p. Hence, this study aims to explore the interaction among miR-30a-5p, WWP1, and NF-κB and their roles in the regulation of glioma development. We found decreased WWP and increased miR-30a-5p expression and p65 phosphorylation in glioma tissues. Furthermore, WWP1 mRNA level was negatively correlated with miR-30a-5p expression in glioma tissues. Interestingly, miR-30a-5p targeted WWP1 expression. Additionally, NF-κB p65 overexpression increased miR-30a-5p expression through direct binding of NF-κB RelA subunit to the promoter of miR-30a-5p. We also confirmed that WWP1 overexpression decreased phosphorylation of NF-κB p65. Importantly, miR-30a-5p promoted glioma cell proliferation, migration, and invasion via targeting WWP1. Furthermore, NF-κB p65 overexpression inhibited WWP1 expression and promoted glioma cell malignant behaviors via inducing miR-30a-5p transcription. Moreover, WWP1 overexpression decreased miR-30a-5p expression and inhibited glioma cell malignant behaviors via inhibiting NF-κB p65. Our further assay showed that WWP1 inhibited in vivo growth of xenograft tumors of glioma cells, accompanied with a decrease in miR-30-5p expression and phosphorylation of NF-κB p65. In conclusion, there is a "miR-30a-5p-WWP1-NF-κB" positive feedback loop, which plays an important role in regulating glioma development and might provide a potential therapeutic strategy for treating glioma.